Policy implications of the spatial and structural relationships of the informal and formal business sectors in urban Nigeria : the case of Enugu (1990-2010) - Onyebueke, Victor Udemezue (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.